INOVASI PELAYANAN PERDAGANGAN EKSPOR IMPOR OLEH DINAS PERDAGANGAN PROV JATIM MELALUI E- SKA - Muhammad Fikri Fatchul Yaqien; Ismail Ismail; Fierda Nurany (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This research aims to understand the world of international trade/export-import and its benefits and factors. The types of this research are data reduction, data presentation, and drawing conclusions because this research is descriptive qualitative in nature, the location of this research is at the East Java Province Disperindag Office. The technique of collecting data through a number of (documented information) in the form of written documents or recordings is known as the documentary technique. The results of the research that the researchers obtained were that International Trade Policy is the actions taken by a country to influence the ongoing international trade. In this case, it relates to actions on current accounts rather than the international balance of payments, especially regarding exports and imports of goods/services. Government Regulation Number 41 of 2007 concerning Regional Apparatus Organizations, the East Java Province Industry and Trade Service is established based on East Java Province Regional Regulation Number 9 of 2008 concerning the Organization and Work Procedures of the East Java Province Regional Service which is led by a Head of Service and assisted by a Service Secretary; 7 (seven) Fields (Standardization and Design of Industrial Products, Agro & Chemical Industry, Metal Industry, Textile & Miscellaneous Machinery, Electronics & Telematics Transportation Equipment Industry, Domestic Trade, International Trade, and Metrology Functional Position Groups and Service Technical Implementation Units, then Therefore, the East Java Provincial Industry and Trade Service was established based on regional regulation number 11 of 2016 concerning the formation and composition of regional apparatus which is led by a service head who is assisted by a service secretary. Keywords: Export-import, Trade, E-SKA.